2011
DOI: 10.1177/0034355210392241
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Employment Outcomes for Vocational Rehabilitation Consumers With HIV/AIDS: 2002–2007

Abstract: This study examined the predictability of two employment outcomes—employment status and weekly earnings at closure— from consumer demographic, medical, and service variables for multiple groups of vocational rehabilitation (VR) consumers with HIV/AIDS retrieved from the RSA-911 data for fiscal years 2002 through 2007. A logistic regression analysis was used to determine predictors of employment status at closure across years, and a multiple regression analysis was conducted to identify predictors of weekly wag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The study indicated that for people who had negative employment experience for a long time, choosing low-paying jobs or not to work on purpose could be out of concern for securing their disability benefits. This effect has been widely examined in people with other chronic disabilities Dutta et al 2008;Jung and Bellini 2011).…”
Section: Vocational Servicesmentioning
confidence: 99%
“…The study indicated that for people who had negative employment experience for a long time, choosing low-paying jobs or not to work on purpose could be out of concern for securing their disability benefits. This effect has been widely examined in people with other chronic disabilities Dutta et al 2008;Jung and Bellini 2011).…”
Section: Vocational Servicesmentioning
confidence: 99%
“…In contrast, co-occurring psychiatric disabilities start to show a negative relationship with being employed when individuals are approaching their adulthood, whereas the receipt of cash or medical benefits always increases the risk of being unemployed. In fact, the adverse effect of receiving cash or medical benefits on employment outcomes has been widely discussed among persons with different disabilities Jung and Bellini 2011). It is indicated that for those individuals who are at high risk of being unemployed or underemployed, they might weigh the financial benefits of paid work against the real possibility of losing disability-related benefits (Dutta et al 2008).…”
Section: Differences In Service Usage Pattern Across Age Groupsmentioning
confidence: 99%
“…Quite a few existing rehabilitation studies have also indicated that job-related services, especially job placement services, are strongly associated with better employment outcomes for most disability groups, including individuals with ASD (Bolton et al 2000;Dutta et al 2008;Jung and Bellini 2011;Jung et al 2010;Migliore et al 2012;Schaller and Yang 2005). With the exception of the adult group, additional VR services were found to be significant predictors for the transition youth group and the transition young adult group.…”
Section: Differences In Service Usage Pattern Across Age Groupsmentioning
confidence: 99%
“…As HIV/AIDS has shifted from an acute disease to a chronic illness, which can lead to a disability (Conyers, Chiu, Shamburger-Rousseau, Johnson, & Misrok, 2014; Swendeman, Ingram, & Rotheram-Borus, 2009), rehabilitation counselors and educators have responded to the needs of individuals with HIV through education, research, and practice (Conyers, 2005; Hergenrather, Geishecker, Clark, & Rhodes, 2013; Hergenrather, Rhodes, & McDaniel, 2005; Jung, Schaller, & Bellini, 2010; Kohlenberg & Watts, 2003). One reflection of this increased need for rehabilitation services was the 67% increase in the numbers of consumers with HIV exiting the public vocational rehabilitation (VR) program from 2002 through 2007 (Jung & Bellini, 2011). In a study of public VR counselor attitudes about serving consumers with AIDS, Hergenrather et al (2005) reported that 55.6% of respondents noted that they served consumers with AIDS.…”
Section: Introductionmentioning
confidence: 99%